An overview of studies on food insecurity during and after the COVID-19 pandemic: a systematic review - Yusuf, Muhammad-Bashir Owolabi; Lawal, Saheed Oluwaseun; Mahadi, Nur Farhah (Sciendo, 2025)
Research background: Since the COVID-19 pandemic, disruptions in food production have highlighted the renewed importance of ensuring food security. This context motivates the investigation of food insecurity during and after the epidemic. Purpose: The purpose of this study is to conduct a comprehensive analysis of food insecurity research, utilizing bibliometric and thematic analysis techniques. The aim is to identify prevalent approaches or models employed in studying food insecurity and to track the evolving trends in research on food insecurity during and after pandemics. Research methodology: We conducted a systematic search of relevant articles published in scholarly journals between 2020 and 2023, utilizing the Scopus and Web of Science databases. A total of 146 publications were included in the study. Bibliometric analysis was performed using the R-based Bibliometrix library to analyze the characteristics of the literature. Results: Our analysis reveals the diverse range of models and methodologies employed to study food insecurity. Descriptive research and the Logit model emerge as consistently utilized approaches, with the United States and Asia leading in model and methodology adoption. Furthermore, the bibliometric analysis indicates a rapid growth in scholarly interest in food insecurity, demonstrating a global inclination towards understanding this complex issue. Novelty: This study contributes to the existing literature by providing insights into the current landscape of food insecurity research during and after pandemics. It highlights the prevalent approaches and trends in this field, shedding light on areas of focus and potential avenues for future research and collaboration among scientists worldwide.